A Novel Five Phase DSTATCOM for Industrial Loads - Prasad Rao, K. P.; Varma P, Srinivasa (International Journal of Engineering and Technology, 2018)
Now-a-days most of the industries want to earn more profit. It is possible with Five Phase Induction Machines. It attains the more efficiency because of its five phase winding arrangement. These machines are specially design for industries. Making the conversion of five phase supply from three phase supply with the help of transformer scheme which is specially designed. Generally, power quality problem like voltage sag occurs because of sudden changes in loads. In this paper, as a remedy, five phase DSTATCOM (Distribution Static Compensator) with PWM technique is opted to mitigate the voltage sag as power quality problem by injecting the currents in to the system. The MATLAB simulation results represent the effectiveness of five phase DSTATCOM with PWM technique.